Cyperaceae of Ukraine: taxonomy and linear classification - Danylyk, Ivan M.; Koopman, Jacob (Phytotaxa, 2023)
In this research the family Cyperaceae in Ukraine has critically been revised. An up-to-date classification of all taxa is presented, i.e. one subfamily (Cyperoideae), 13 tribes, 16 genera, and 148 species. The genus Cyperus s.l. includes now Acorellus, Dichostylis, Juncellus, Mariscus, Pycreus, and Torulinium, which were previously considered as separate genera. However, the genera Schoenoplectus and Schoenoplectiella are listed by us as recognised taxa. A new combination in the rank of section, Hostianae (Carex: Cariceae), is given. The basic unit of our classification is the species, although subspecies and varieties are indicated to cover intraspecific heterogeneity when necessary.